What would happen if UK residents stopped having babies?. Issue 2 (April 2016) - Timaeus, Ian
Abstract : What would happen if UK residents stopped having babies? Demographer Ian Timæus offers some projections Abstract : The Year 6 children of Milwards Primary School ask: If current UK residents stopped having babies, how long would it take for the human population to drop to zero?